The Encyclopedia of Flora on Curiak Island to Improve Critical Thinking Skills of Science Education Students - Mella Mutika Sari; Ratna Yulinda; Desy Purwasih (Jurnal Penelitian Pendidikan IPA, 2024)
This research aims to produce a flora encyclopedia product on Curiak Island that is suitable for improving critical thinking skills. Â Type of Educational Design Research (EDR) research using Tessmer formative evaluation design. The formative evaluation used consists of four stages, namely the self-evaluation stage, expert review, one-to-one evaluation, and small group evaluation. Collecting product validation data using an encyclopedia assessment instrument. Data regarding validity is collected through an encyclopedia validation sheet by giving a score of 1, 2, 3, or 4 (1 = not good, 2 = quite good, 3 = good, and 4 = very good). Critical thinking assessment use essay with four indicators. The findings show that the product developed is feasible in terms of material, media and language. The test results show that there is a significant difference in students' critical thinking abilities before and after learning. Apart from that, the analysis indicator in critical thinking skills obtained the highest score in the medium category. These findings illustrate that the effectiveness of product expectations is effective in improving students' critical thinking abilities.